Architecture as a projection of multiplicities - Kristanti Dewi Paramita (Department of Architecture Faculty of Engineering Universitas Indonesia, 2022)
The architectural discussion of multiplicity moves beyond the preoccupation with architecture as a fixed, conclusive, and eternal entity. The collection of articles in this issue of ARSNET investigates the multidimensionality of architecture. The explorations in this issue span from the discussion of multi-layered meaning and temporalities of architecture, to the dynamic representation and spatial operation of multiplicities. Through inquiries on multiplicity-driven design methods, this issue projects the expanded and open field of architecture, appreciating the different forces and processes of society.